Plight of Fundamental Facilities in Government schools of Faisalabad - Shafqat RasooL (JELM, 2023)
The present study was designed to investigate the plight of the basic facilities in Government schools situated in district Faisalabad. The study was delimited to the schools of sub division Jaranwala. The purpose of this study was to find out the present status of basic facilities in schools along with difference of basic facilities in locality, gender, and level wise schools of Jaranwala. A total of 60 schools were selected as sample through stratified sampling technique. The research study was survey type as research method. Self-constructed Likert scale was used as research instrument to collect data. The data were analyzed by using Chi square test. The study concluded that majority of the schools faced same issues regarding shortage of basic facilities such as shortage of sufficient facility of toilets, drinking water, classrooms, furniture, staff, labs etc. The condition of schools in cities are much better than schools in rural areas.